The Role of Lore in Purchase Decisions for Mecha Plastic Model - Iswanto, Rendy; Suharto, Suharto (VCD, 2025)
Nowadays, Japanese pop culture is growing rapidly in Indonesia, encompassing Anime, Manga, and Video Games originating from Japanese subcultures. Anime, Manga, and Video Games are not only popular in Japan and Indonesia but are also adored by people from many other countries, making Japanese pop culture a global phenomenon. Like anime films, manga has various genres, one of which is the mecha genre. The mecha genre is a sci-fi or fantasy genre that involves robot characters, commonly referred to as mecha. One of the most successful mecha anime series that has produced numerous merchandise items is Mobile Suit Gundam, Gundam has led to the creation of various merchandise, particularly Gunpla (Gundam plastic models), which are often supported by rich lore through anime and manga. In contrast, newer Chinese mecha model manufacturers frequently release products without any accompanying narrative or backstory. The purpose of this study is to analyze how the presence or absence of lore influences consumer purchasing decisions for mecha plastic models. Through qualitative analysis, the research reveals it was found that the presence of a backstory or lore does not significantly influence the consumer’s decision as long as the design, price, and quality of the product offered can compete with Japanese model kits. However, lore can serve as an added value for model kits from China, as this background story provides a deeper understanding for the buyer about the story behind the product.